Fréquentation des cultures par les abeilles mellifères et sauvages : Synthèse des connaissances pour réduire le risque d'intoxication aux pesticides - Decourtye, Axel (2016)
In France, a derogation to pesticide regulation allows spraying on blooms with insecticides or acaricides bearing the bee label (mention « Abeilles »), but only when no bees are foraging on crops. Nevertheless, no decision rule is available for farmers to assess bees’ absence on the crop. To fill this gap, the Ministry of Agriculture initiated a reflection about environmental and climatic factors influencing the presence of forager bees. This review takes an inventory of data available about foraging activity according to environment or weather. Decision rules based on such criteria appear inappropriate. Only nocturnal sprays of pesticides on crops significantly reduce the risk of bees’ exposure to chemicals.